Finite-Time Chaos Control of a Complex Permanent Magnet Synchronous Motor System - Xiaobing Zhou; Murong Jiang; Xiaomei Cai (Abstract and Applied Analysis)
This paper investigates the finite-time chaos control of a permanent magnet synchronous motor system with complex variables. Based on the finite-time stability theory, two control strategies are proposed to realize stabilization of the complex permanent magnet synchronous motor system in a finite time. Two numerical simulations have been conducted to demonstrate the validity and feasibility of the theoretical analysis.